The effect of local anaesthetic agents on opioid use and recovery in patients undergoing open heart surgery: a randomized controlled study - Hatice AZİZOĞLU; Mehmet AŞAM; Zeynep GÜRKAN; Yasemin BOZKURT; Canan DEMİR (BMC Cardiovascular Disorders)
Abstract Background After open heart surgery, patients experience high levels of pain at the sternotomy incision site and around the chest tube(s), affecting their recovery. This study was conducted to determine the effects of local anesthetic application around the sternotomy incision site and chest tube(s) on the amount of opioids used and recovery after surgery in patients undergoing open heart surgery. Methods This randomized controlled experimental study was conducted with a total of 60 patients, with 30 patients in the experimental group and 30 patients in the control group. In the experimental group, LIDOFAST 40 mg/2 ml + 0.025 mg/2 ml, a local anesthetic agent, was applied to the postoperative sternotomy incision site and around the chest tube(s) in addition to routine treatment. Patients in the control group received only routine treatment. Data were collected using the “Descriptive Characteristics Form” and the “Postoperative Recovery Index”. Results It was observed that postoperative pain started later, opioid consumption decreased, and postoperative recovery was faster in the experimental group. As the number of chest tubes increased, recovery was delayed in all groups, and as the number of opioids used increased, postoperative recovery was negatively affected in the control group. Conclusions In this study, local anesthetic application to the sternotomy incision site and around the chest tubes after open heart surgery was found to reduce postoperative opioid consumption and positively affect recovery. Trial registration Current Controlled Trials NCT06642077 (Retrospectively registered).